The Relationship Between Maternal Weight Gain and Newborn Weight With the Frequency of Stunting in South Central Timor District (TTS) - Henukh, Dina; Siti Nur Asyah Jamillah Ahmad; Aning Pattypeilohy (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
During pregnancy, mothers are prone to experiencing nutritional problems. This problem can be fatal and exceptionally perilous for both the fetus and the mother. Malnutrition in pregnant women encompasses a huge enough affect on the growth process of the fetus and the child to be born, one of which is stunting. Toddlers' stunting in NTT is ranked 34th in Indonesia with a short presentation of 22.30% and very short 18.00%, while the incidence of stunting in TTS district reaches 57.3%. The point of the study was to analyze the relationship between maternal weight gain and newborn weight with the frequency of stunting. This type of research used case control with retrospective approach. The population of all children under five with incidence of stunting and non-stunting, the subjects of the study were 200 samples in 8 Public Helath Center in TTS district. Data collection using a questionnaire and with univariate and bivariate analysis and tested using the Chi-square test. The results showed that maternal weight gain during pregnancy in stunting infants had a weight gain that was not according to the recommendation, which was 55%, experiencing weight gain as recommended during pregnancy was 45%, while the weight of newborns who were stunted had an abnormal weight gain 60 % and the normal weight gain is 40%. After doing the Chi-Square test, the Asymp was obtained. Sig. is 0.000 <α (0.05). Therefore, it can be concluded that there’s a critical relationship between maternal weight gain during pregnancy and birth weight on the incidence of stunting.